The Educational Philosophy of Boko-haram; Analysis from Islamic Perspective - Nasirudeen Abdulrahim Adeyanju; Muhammad Umar; Abdulraheem Muhammad Sunusi (USIM Press, 2024)
Vol. 32 (2020): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [December 2020]